AND THE “BAIANA” IS BORN: RELATIONS BETWEEN CARMEN MIRANDA, IDENTITY AND STATE - Macedo, Káritha (2011)
This study intends to analyze the construction of a Brazilian national identity on the figure of Carmen Miranda and her “baiana”. It debates the creation of the character that features Carmen and why she received the status of  “national symbol” and synonym of  “Brazilian identity”. Therefore, it seeks other national elements that supported this understanding and analyzes the performance of Carmen in “O que é que a baiana tem” in the film “Banana da Terra” (1939), the first time that she wore the character. However in the same year the film was released, Carmen Miranda left to the United States, and there the “baiana” became the icon we know today. Therefore, in order to understand how she became a myth, it raises some points of her career there. The research was carried out from Carmen Miranda’s broadcasted images, her filmography, the available literature, print and digital media, and virtual collections.